2022
DOI: 10.1007/s00424-022-02690-y
|View full text |Cite
|
Sign up to set email alerts
|

Renal blood flow and oxygenation

Abstract: Our kidneys receive about one-fifth of the cardiac output at rest and have a low oxygen extraction ratio, but may sustain, under some conditions, hypoxic injuries that might lead to chronic kidney disease. This is due to large regional variations in renal blood flow and oxygenation, which are the prerequisite for some and the consequence of other kidney functions. The concurrent operation of these functions is reliant on a multitude of neuro-hormonal signaling cascades and feedback loops that also include the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 102 publications
(101 reference statements)
0
15
0
Order By: Relevance
“…Since the shunt and diffusion of oxygen between venous and arterial vessels that run in close parallel contact, the oxygen tensions of renal tissue are in fact comparatively low. Thus, the kidneys are sensitive to changes in systemic oxygenation [ 32 ]. Anemia might accelerate renal function decline by inducing tubulointerstitial hypoxia [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the shunt and diffusion of oxygen between venous and arterial vessels that run in close parallel contact, the oxygen tensions of renal tissue are in fact comparatively low. Thus, the kidneys are sensitive to changes in systemic oxygenation [ 32 ]. Anemia might accelerate renal function decline by inducing tubulointerstitial hypoxia [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…6a, b). It has been shown that renal blood flow velocity correlates to renal tissue oxygenation 62,63 . To showcase the capability of the interleaved PA/SC-ULM imaging, we conducted an in vivo oxygen-challenge experiment in mice to mimic various scenarios of tissue oxygenation and image the corresponding blood velocity change.…”
Section: In Vivo Dual Pa/fast Ulm Imaging Of a Mouse Kidneymentioning
confidence: 99%
“…Normal organs also may have a wide range of pO 2 distribution. The pO 2 in renal cortical tissue falls within the range of 20 to 60 mm Hg, whereas the pO 2 values in the outer and inner medulla are in the range of 15 to 30 mm Hg and <15 mm Hg, respectively 19,20 . BOLD‐MRI has been used to detect R 2 value changes in the cortex and medulla 21 .…”
Section: Introductionmentioning
confidence: 99%